A 2017–2019 Update on Acute Intoxications and Fatalities from Illicit Fentanyl and Analogs. Issue 6 (29th August 2020) - Brunetti, Pietro; Pirani, Filippo; Carlier, Jeremy; Giorgetti, Raffaele; Busardò, Francesco Paolo; Lo Faro, Alfredo Fabrizio
Abstract: The aim of this review was to report the most recent cases of acute intoxication, fatalities and "driving under the influence" cases, involving illicit fentanyl and its newest analogs. When available, information on age, sex, circumstances of exposure, intoxication symptoms, cause of death (if applicable) and toxicology results from biological fluid testing was described. Scientific publications reporting fatalities or acute intoxications involving use of fentanyl derivatives were identified from PubMed, Scopus and institutional/governmental websites from January 2017 up to December 2019. The search terms, used alone and in combination, were as follows: fentanyl, street fentanyl, analogs, compounds, derivatives, abuse, fatality, fatalities, death, toxicity, intoxication and adverse effects. When considered relevant, reports not captured by the initial search but cited in other publications were also included. Of the 2890 sources initially found, only 44 were suitable for the review. Emergent data showed that the most common analogs detected in biological samples and seized materials are acetylfentanyl, acrylfentanyl, butyrfentanyl, carfentanil, cyclopropylfentanyl, fluorofentanyl, 4-fluorobutyrfentanyl, 4-fluoroisobutyrfentanyl, furanylfentanyl, 2-methoxyacetylfentanyl, 3-methylfentanyl and ocfentanil. These compounds were frequently administered in association with other illicit substances, medicinal drugs and/or alcohol; patients and the victims often had a previous history of drug abuse. The trend of fentanyl analogs is rapidly evolving with illicit market fluctuations. Since information about potency and lethal dosage are frequently unknown, it is important to identify the new trends for further investigation on therapeutic use, toxicity and fatal doses, and implement public health measures. Recently marketed fentanyl analogs such as crotonylfentanyl and valerylfentanyl were not involved in intoxications to date, but should be carefully monitored. Many intoxications and fatalities might have gone unnoticed, and research efforts should focus on metabolite identification studies and the implementation of updated and comprehensive analytical methods